Are orthostatic vital signs useful in detecting dehydration and hypovolemia in adults?. Issue 9 (September 2016) - Mott, Timothy; Allen, Rebecca
Abstract : Evidence‐Based Answer : Heart rate is the only orthostatic vital sign (OVS) that correlates with dehydration (change in total free water) for adult patients in the emergency department (ED) (SOR: B, prospective observational study). OVSs vary widely in euvolemic patients, making "normal" values of uncertain utility (SOR: C, observational study). OVSs do not reliably predict modest volume (intravascular) losses (SOR: C, expert opinion).